Effects of recombinant interferon-gamma and chemotherapy with isoniazid and rifampicin on infections of mouse peritoneal macrophages with Listeria monocytogenes and Mycobacterium microti in vitro. - Khor, M. (1986)
The effect of recombinant murine interferon-gamma (IFN-gamma) on the growth of Listeria monocytogenes for 4 h and Mycobacterium microti for up to 3 days in monolayers of peritoneal macrophages from BALB/c mice was examined by serial viable counts of cell-associated bacteria. Macrophages pretreated with 10 u IFN-gamma per ml were bacteriostatic and with 100 u or 1000 u per ml were bactericidal against L. monocytogenes. Addition of IFN-gamma 3 days before infection caused monolayers to be bactericidal against M. microti mainly during the first 15 min after infection. This was just evident with 10 u IFN-gamma per ml and greater with 100 u or 1000 u per ml. If IFN-gamma was added when phagocytosis of M. microti was complete, about 2 h after infection, its action was only bacteriostatic, the viable counts remaining stationary while those of unexposed monolayers increased. IFN-gamma 100 u per ml added before infection did not alter the bactericidal activity of rifampicin 10 mg/l, nor did it alter the killing curves for isoniazid 1 mg/l or for rifampicin 10 mg/l if added after completion of phagocytosis.